The advanced lung cancer inflammation index predicts chemotherapy response and infection risk in multiple myeloma patients receiving induction chemotherapy - Cheng, Jie; Li, Qianyuan; Xiao, Sheng; Nie, Lu; Liao, Jianping; Jiang, Qingjie; Xiang, Biyu; Zhang, Hongfei; Jiang, Yanhong; Yao, Chenjiao (Frontiers in Genetics, 2022)
Objective: The study aim to the clinical significance of advanced lung cancer inflammation index (ALI) in predicting the prognosis, chemotherapy response and infection risk in newly-diagnosed multiple myeloma (MM) receiving induction therapy. Methods: A retrospective analysis, consisting of clinical characteristics and laboratory examinations, was performed on 111 newly diagnosed MM patients in the Hematology Department of the Third Xiangya Hospital of Central South University from January 2014 to March 2020. We first determined the relationship between ALI and overall survival (OS), as well as clinical and laboratory parameters. Secondly, the predictive factors for chemotherapy response were analyzed by univariate and multivariate regression analysis. Thirdly, a univariate regression analysis of risk factors was performed using infection as the evaluable outcome. Results: Of the 111 evaluable patients, the low ALI group (<32.7) had significantly poorer survival compared to the high ALI group ( 51 months versus 77months), Multivariable analyses showed that advanced age, chemotherapy response, and serum calcium were independent prognostic factors for OS. The efficiency of chemotherapy in the high ALI group (89.3%) was better than low ALI group (42.2%) (P < 0.001), the multivariate analysis suggested that only ALI (HR: 0.110, 95% CI [0.035-0.350],p = 0.000) was independently predictive effect in evaluating the efficiency of induction chemotherapy. 40 patients (36.04%) represented infection after induction chemotherapy. Univariate analysis suggested that low ALI and abnormal renal function increased the risk of infection for those newly-diagnosed MM patients. Conclusion: Our study confirmed that ALI is not only a prognostic biomarker for newly diagnosed patients but also predicts the chemotherapy efficacy of the newly diagnosed MM patients receiving induction therapy.